The Impact of Accounting Information Systems (AIS) on Firm Performance: Empirical Evidence in Turkish Small and Medium Sized Enterprises - ESMERAY, Azize (International Review of Management and Marketing, 2016)
This study is based on empirical evidence at measuring the relationship between the use of the Accounting Information Systems (AIS) by the Small and Medium Sized Enterprises (SMEs) in Kayseri-Turkey, and firms’ improved performance indicators. Kayseri is one of the most successful furniture-making centers in Turkey and it earned more than a billion dollars in export revenues in 2007. The data obtained from interviews with 60 firms in the organized industrial zone is analyzed by Generalized Least Squares (GLS). It is found that there is positive and statistically significant relation between the use of AIS and educational status of managers. Moreover, as the number of employees rises, the use of AIS also increases. Furthermore, a positive relation is found between the use of AIS and growth (Sale, Customer and Revenue). Keywords: AIS, Small and Medium Sized Enterprises (SMEs), GLS. JEL Classifications: L00, M